What travel motivational factors influence Muslim tourists towards MMITD?. Issue 1 (6th March 2017) - Rahman, Muhammad Khalilur; Zailani, Suhaiza; Musa, Ghazali
Abstract : Purpose: The World Islamic Tourism Mart in Malaysia has been attracting Muslim tourists from all over the world to choose Malaysia as their Islamic tourism destination. This paper aims to implement the concept of the travel career ladder (TCL) with the main purpose of the antecedents of travel motivation toward Malaysia for Islamic tourism destination (MMITD). Design/methodology/approach: The theoretical model was tested using the structural equation modeling technique with partial least squares. A self-administered questionnaire was designed, distributed and collected from 180 effective participants who had visited Malaysia. Findings: The findings revealed that the Islamic compliance with self-esteem needs, the Islamic compliance with relationship needs and the Islamic compliance with physiological needs have significant effects on Malaysia My Islamic tourism destination. Research limitations/implications: The scope of this research paper is limited to TCL including the Islamic compliance issues with self-fulfillment, self-esteem, relationship, safety and physiological needs. A small sample size was obtained with participants from the Muslim countries. A future study should be comprehensively conducted on larger and diverse sampling methods with participants from the Muslim and the non-Muslim major countries, as this paper particularly discusses the theoretical and managerial implications for the anticipated future studies. Originality/value: The study yet attempts on the part of academicians in Malaysia, what travel motivational factors influence Islamic tourists to travel MMITD. Based on the previous literature and researcher's experience, it is a new phenomenon and investigation on MMITD.